RETRACTED: Leukocyte telomere length and obesity in children and adolescents: A systematic review and meta-analysis - Farhangi, Mahdieh A.; Lame, Amir-Hossein (Frontiers in Genetics, 2022)
Background: Several studies have revealed the negative effects of adiposity on telomere length shortening. However, the results of the studies assessing the negative relationship between obesity and leukocyte telomere length (LTL) are not consistent. This systematic review and meta-analysis are aimed to pool the results of articles assessing the relationship between obesity and LTL among children and adolescents. Methods: To retrieve the related studies, four online databases including PubMed, Embase, ProQuest, and Scopus were searched until May 2022. Observational studies evaluating the relationship between obesity and LTL among apparently healthy children and adolescents (aged ≤18 years) were included in the study. We considered the studies that had reported a mean ± standard deviation of LTL. The random-effects model was used to assess the pooled weighted mean difference (WMD) and a 95% confidence interval (CI). Results: The search yielded seven studies from an initial 3,403 records identified. According to the results of seven articles with 4,546 participants, obesity was associated with LTL shortening among children and adolescents (WMD = −0.081; 95% CI: −0.137 to −0.026; p = 0.004; I2 = 99.9%). Also, no publication bias was observed. According to the results of subgrouping, significant results were only attributed to the studies conducted in Europe, with high quality scores, among overweight and obese adolescents, with a baseline LTL lower than 1, and performed in community-based school settings. Also, according to the subgrouping and meta-regression results, the obesity definition criteria and baseline LTL were the possible sources of between-study heterogeneity. Conclusion: We observed shorter LTL among overweight and obese children and adolescents. To obtain more reliable results, further longitudinal prospective studies with large sample sizes and more consistent and accurate definitions of obesity are required.